2020
DOI: 10.1002/lary.28831
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of the Standardized Cosmesis and Health Nasal Outcomes Survey After Rhinoplasty

Abstract: Objectives/Hypothesis To explore the natural history of nasal obstruction and cosmesis following rhinoplasty by utilizing the Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS). Study Design Retrospective chart study. Methods This study was carried out at a tertiary referral center, preoperative and postoperative Nasal Obstruction Symptom Evaluation (NOSE), SCHNOS‐Obstruction (SCHNOS‐O), and SCHNOS‐Cosmesis (SCHNOS‐C) scores in patients who underwent rhinoplasty for functional, cosmetic, or both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…They determined that Quantifying the Subjective Experience of Nasal Obstruction Meyer, Most improvement in nasal breathing symptoms and cosmesis could be identified as early as 1 to 2 months postoperatively and sustained greater than 12 months. 43 This study further supports implementation of the SCHNOS as a patient care tool because it supports the notion that even patients with comorbid inflammatory nasal disease (e.g., allergic rhinitis, irritant exposure, etc.) reported significant improvement in their nasal obstruction symptoms postoperatively.…”
Section: Patient-reported Outcome Measuressupporting
confidence: 75%
See 1 more Smart Citation
“…They determined that Quantifying the Subjective Experience of Nasal Obstruction Meyer, Most improvement in nasal breathing symptoms and cosmesis could be identified as early as 1 to 2 months postoperatively and sustained greater than 12 months. 43 This study further supports implementation of the SCHNOS as a patient care tool because it supports the notion that even patients with comorbid inflammatory nasal disease (e.g., allergic rhinitis, irritant exposure, etc.) reported significant improvement in their nasal obstruction symptoms postoperatively.…”
Section: Patient-reported Outcome Measuressupporting
confidence: 75%
“…Kandathil et al evaluated the natural history of SCHNOS scores in patients who underwent rhinoplasty for functional, cosmetic or combined reasons. They determined that improvement in nasal breathing symptoms and cosmesis could be identified as early as 1 to 2 months post-operatively and sustained >12 months [44]. This study further supports implementation of the SCHNOS as a patient care tool because it supports the notion that even patients with co-morbid inflammatory nasal disease (e.g., allergic rhinitis, irritant exposure, etc.)…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…Kandathil et al showed that the significantly improved SCHNOS scores were achieved in the early postoperative follow-up, and remained sustained through postoperative late-term without a significant difference, in cosmetic and functional rhinoplasty patients. 22 In another report, Kandathil et al emphasized that NOSE scores improved significantly as early as 1 month postoperatively following functional rhinoplasty; however, these shortterm scores were not significantly different compared with late-term. 23 Similarly, Fuller et al reported no significant differences between follow-up time point scores after the postoperative second month within the NOSE scale in patients who underwent functional rhinoplasty with SpG.…”
Section: Discussionmentioning
confidence: 95%
“…Patients may be categorized as having mild (< 33.3), moderate (33.3-66.6), and severe (> 66.6) aesthetic distress based on the SCHNOS-C. A score of 30 on the SCHNOS-C differentiated patients with and without aesthetic concerns. 72 MCID differences have been determined to be 28 points for the SCHNOS-O and 18 points for the SCHNOS-C. 73 In a retrospective study of 302 patients, mean scores were shown to decrease after functional septorhinoplasty from 73 (SD 18) to 28 (SD 26) for SCHNOS-O, and 30 (SD 28) to 5 (SD 9) for SCHNOS-C. 50 The SCHNOS-C score has been shown to correlate with Body Dysmorphic Disorder Questionnaire-Aesthetic Surgery (BDDQ-AS) scores, a validated instrument for BDD screening. The SCHNOS-C score greater than 73 had a high sensitivity and specificity of also screening positive for BDD with the BDDQ-AS.…”
Section: Standardized Cosmesis and Health Nasal Outcomes Surveymentioning
confidence: 99%